Penerapan Model Pembelajaran Aptitude Treatment Interaction (ATI) Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IV di SD Negeri Sungai Tonang Kec. Kampar Utara - Insani, Fajrul; Witri, Gustimal; Putra, M. Jaya Adi (Indonesian Research Journal on Education, 2021)
The background of this study is the low mathematics learning outcome of IV grade students of SDNegeri 015 Sungai Tonang with an average score of 61.95, subpar to the KKM (minimum criteriaof mastery) of the school, which was 70.00. This study aims to determine the increase inmathematics learning outcomes of IV grade students in SD Negeri Sungai Tonang, North KamparDistrict, odd semester 2020/2021 after the implementation of Aptitude Treatment Interaction (ATI)learning model. This type of research is Classroom Action Research (CAR) which is carried out intwo cycles with the stages of planning, implementing, observing, and reflecting. The subjects ofthis study were 20 IV grade students of SD Negeri 015 Sungai Tonang, North Kampar District, inthe odd semester of 2020/2021 academic year. The data collection techniques are in the form ofobservations and tests. The average mathematics score before the application of the AptitudeTreatment Interaction (ATI) learning model was 61.95, then increased to 68.00 in the first cycleand 73.50 in the second cycle. The results showed that by implementing the Aptitude TreatmentInteraction (ATI) learning model, the IV grade students of SD Negeri 015 Sungai Tonangmathematics score could be improved.